The impacts of putting the Zaporizhzhia Nuclear Power Plant in the line of fire - Christos Tsagkaris; Lolita Matiashova; Anna Isayeva (Wiley, 2022)
Abstract The armed forces of the Russian Federation captured the Zaporizhzhia Nuclear Power Station after their invasion to Ukraine in February 2022. In early August 2022, reports about shelling of the station ignited fear of a nuclear accident. Simultaneously, the disruption in the generation of electricity from nuclear energy has fueled a notable increase in the price of oil. The compounding effect of these developments on global health includes acute and chronic radiation exposure, food insecurity due to the potential contamination of the environment and the rise in the cost of essential commodities, and limited access to healthcare. International and national governance bodies need to take action in order to mitigate the effects of this incident on health and prevent similar events in the future.